Pola Hubungan Ruang Rumah Sakit Umum Daerah Tebing Tinggi terhadap Peraturan Menteri Kesehatan - dasrizal dasrizal; Mei Brilian Harefa; Alif Saum Rizalitaher; Junianty Dahnita br Purba; Elia Yo Sepa br Ginting (Jurnal Syntax Admiration, 2024)
In the relationship of space, the architect makes a precondition of how each space should relate and the type of relationship. The pattern of hospital room relationships has been regulated in the regulation of the Minister of Health. This study aims to analyze the level of suitability of the hospital room relationship with the regulations of the Minister of Health. The object of the research used is the Kumpulan Pane Regional General Hospital or abbreviated as RSKP, located in the city of Tebing Tinggi, Serdang Bedagai Regency, North Sumatra Province. This research is a quantitative research, with data obtained through direct observation and juxtaposed with the Regulation of the Minister of Health. The results of observations at the location of the research object found that the spatial relationship pattern between hospital buildings did not meet the standard of spatial relationship pattern contained in the Regulation of the Minister of Health. This study has a conclusion that some of the buildings in the hospital do not meet the existing regulatory standards so that they need to be adjusted. The targeted output is an accredited journal.